Prenatal ruxolitinib treatment improved muscle strength but showed no impact on the neurobehavioral and electrophysiological traits in adult mice - Azimzadeh, Mansour; Lim, Shi En; Mazhar, Nurul Syahirah; Ling, King Hwa; Cheah, Pike See (Pleiades Publishing, 2024)
The JAK/STAT signalling pathway is essential for cell communication and gene expression, particularly in brain development. Its dysregulation relates to neurological conditions such as Down syndrome and Noonan syndrome, impacting the shift from neuron to astrocyte production. Ruxolitinib, an FDA approved JAK1 and JAK2 inhibitor, is used to treat disorders associated with dysregulated JAK-STAT signaling. This study aimed to evaluate the possible effects of prenatal ruxolitinib treatment on wild-type C57BL/6 mice, their motor skills, neurobehavioral tests, and electrophysiological properties of hippocampal CA1 neurons during adulthood. Pregnant mice were administered non-toxic doses of ruxolitinib (30 mg/kg/day) orally from E13.5 to E20.5, and nine pups were delivered for each untreated and treated group for downstream analyses. Neurobehavioral and electrophysiological experiments were performed on 8.5–10.5-week-old mice. Administering ruxolitinib prenatally significantly improved muscle strength (p < 0.05). However, no changes were observed in learning ability, motor coordination, locomotor function, exploratory and anxiety related behaviour, or recognition memory (p > 0.05). Additionally, there were no significant differences in the input/output (IO) function or paired-pulse paradigm in hippocampal CA1 (p > 0.05). In conclusion, prenatal ruxolitinib treatment in C57BL/6 mice shows no adverse effects on behavioral, learning and memory but enhances muscle strength.